2010
DOI: 10.1073/pnas.1008856108
|View full text |Cite
|
Sign up to set email alerts
|

Complex genetic, photothermal, and photoacoustic analysis of nanoparticle-plant interactions

Abstract: Understanding the nature of interactions between engineered nanomaterials and plants is crucial in comprehending the impact of nanotechnology on the environment and agriculture with a focus on toxicity concerns, plant disease treatment, and genetic engineering. To date, little progress has been made in studying nanoparticle-plant interactions at single nanoparticle and genetic levels. Here, we introduce an advanced platform integrating genetic, Raman, photothermal, and photoacoustic methods. Using this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
363
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(397 citation statements)
references
References 30 publications
22
363
0
3
Order By: Relevance
“…Khodakovskaya et al, (2011) reported insignificant toxicity of graphene in the growth of tomato, although they used only one low concentration (50 μg⁄mL) of chemically functionalized graphene with few layers and with a thickness of 2-5 nm. In a study by Says et al, (2006) carbon nanoparticle functionalization led to a remarkable decline in toxic effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Khodakovskaya et al, (2011) reported insignificant toxicity of graphene in the growth of tomato, although they used only one low concentration (50 μg⁄mL) of chemically functionalized graphene with few layers and with a thickness of 2-5 nm. In a study by Says et al, (2006) carbon nanoparticle functionalization led to a remarkable decline in toxic effects.…”
mentioning
confidence: 99%
“…158 toxic effect of graphene on plant physiology and plant development, indicating possible adverse effects (Khodakovskaya et al, 2011). Khodakovskaya et al, (2011) reported insignificant toxicity of graphene in the growth of tomato, although they used only one low concentration (50 μg⁄mL) of chemically functionalized graphene with few layers and with a thickness of 2-5 nm.…”
mentioning
confidence: 99%
“…Our results indicate that ultrafine MSNs hold considerable potential as nano-carriers of extracellular molecules, and can be used to investigate in vitro gene-delivery in plant cells. Along with developments in the application of nanotechnology from animal science and medical research to plant science research, the impact of engineered nanomaterials on plant systems has attracted increasing attention, the areas including (i) the delivery of fertilizers, herbicides, pesticides and exogenous genes, (ii) the improvement of the growth of plants, and (iii) nanotoxicity research for plant cells [1][2][3][4][5][6][7][8][9][10]. However, compared with mammalian cells, the plant cell wall which is composed of cross-linked polysaccharides (cellulose, hemicelluloses, and pectin) represents an extra barrier surrounding the cell membrane that hinders the passage of nanoparticles into plant cells.…”
mentioning
confidence: 99%
“…Multiwalled carbon nanotubes and zinc oxide NPs were found to be able to stimulate seed germination, thus enhancing the plant's growth in aqueous cultures (Khodakovskaya et al, 2009;Prasad et al, 2012). Moreover, a series of approaches (i.e., genetic, photo-thermal and photo-acoustic methods) were combined to characterize the interactions between multiwalled carbon nanotubes and tomato tissues, providing new insights into the gene transcription regulations of plants under the influence of nanomaterials (Khodakovskaya et al, 2011). However, only colloidal suspensions of NPs were investigated in the previous literature.…”
Section: Introductionmentioning
confidence: 99%